The Knitwear Archive as a Tool to Explore New Technologies - Giovanni Maria Conti; Diego Dani; Martina Motta; Irene Sapuppo; Federica Vacca (ZoneModa Journal)
The knitwear field has been experiencing a significant economic growth and has been going through a strong phase of technological development, driven by merging innovations coming from mechanics, electronics and the digital sector, coherently with the evolution of the Industry 4.0. Two main innovation areas are identified: new manufacturing technologies, developed by knitting machine producers, and virtualization and 3D modeling softwares, enabling virtual garment prototyping on avatars.This paper explores the role of design as a “cultural mediator” between the present and the past and, through a research conducted at the Gianfranco Ferré Research Center, it proposes the use of the archive as a tool to explore the new trajectories of technological innovation in knitwear and to guide them through the perspective of the Industry 5.0, refusing a technocratic idea of the future. Two approaches are highlighted: the ri-materialization of archival pieces through 3D modeling and the reinterpretation of archival material experimenting with new technologies. The research underscores the archive’s role as a tool to anticipate the future and proposes the adoption of a design-oriented approach to fully understand its value, countering a passive consumption of the archive.